Antibiotic use in children before, during and after hospitalisation. Issue 7 (19th April 2022) - Thaulow, Christian Magnus; Blix, Hege Salvesen; Nilsen, Roy Miodini; Eriksen, Beate Horsberg; Wathne, Jannicke Slettli; Berild, Dag; Harthug, Stig
Abstract: Purpose: To investigate ambulatory antibiotic use in children during 1 year before and 1 year after in‐hospital antibiotic exposure compared to children from the general population that had not received antibiotics in‐hospital. Methods: Explorative data‐linkage cohort study from Norway of children aged 3 months to 17 years. One group had received antibiotics in‐Hospital (H+), and one group had not received antibiotics in‐hospital (H‐). The H+ group was recruited during admission in 2017. Using the Norwegian Population Registry, 10 children from the H‐ group were matched with one child from the H+ group according to county of residence, age and sex. We used the Norwegian Prescription Database to register antibiotic use 1 year before and 1 year after the month of hospitalisation. Results: Of 187 children in the H+ group, 83 (44%) received antibiotics before hospitalisation compared to 288/1870 (15%) in the H‐ group, relative risk (RR) 2.88 (95% confidence interval 2.38–3.49). After hospitalisation, 86 (46%) received antibiotics in the H+ group compared to 311 (17%) in the H‐ group, RR 2.77 (2.30–3.33). Comorbidity‐adjusted RR was 2.30 (1.84–2.86) before and 2.25 (1.81–2.79) after hospitalisation. RR after hospitalisation was 2.55 (1.99–3.26) in children 3 months‐2 years, 4.03 (2.84–5.71) in children 3–12 years and 2.07 (1.33–3.20) in children 13–17 years. Conclusions: Children exposed to antibiotics in‐hospital had two to three times higher risk of receiving antibiotics in ambulatory care both before and after hospitalisation. The link between in‐hospital and ambulatory antibiotic exposure should be emphasised in future antibiotic stewardship programs.